2003
DOI: 10.1046/j.1365-2885.2003.00465.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of propofol infusion and propofol/isoflurane anaesthesia in dexmedetomidine premedicated dogs

Abstract: The effects of propofol infusion were compared with propofol/isoflurane anaesthesia in six beagles premedicated with 10 microg/kg intramuscular (i.m.) dexmedetomidine. The suitability of a cold pressor test (CPT) as a stress stimulus in dogs was also studied. Each dog received isoflurane (end tidal 1.0%, induction with propofol) with and without CPT; propofol (200 microg/kg/min, induction with propofol) with and without CPT; premedication alone with and without CPT in a randomized block study in six separate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 23 publications
(41 reference statements)
2
24
0
2
Order By: Relevance
“…However, in one study, dogs recovered slower with propofol TIVA than with propofol/isoflurane anesthesia [6]. The present study showed similar results.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…However, in one study, dogs recovered slower with propofol TIVA than with propofol/isoflurane anesthesia [6]. The present study showed similar results.…”
supporting
confidence: 84%
“…The present study showed similar results. The prolongation of recovery using propofol TIVA is not compatible with the hypothesis that propofol provides lighter anesthetic planes [5,6]. The slower but smoother recovery in dogs with propofol TIVA may be a physio-pharmacologic feature of the agent and requires further investigation.…”
mentioning
confidence: 85%
“…This is similar to a finding in dogs that dexmedetomidine delayed recovery from propofol, but not from isoflurane. 5 Although these authors postulated a pharmacokinetic explanation, Dutta et al 6 showed that the pharmacokinetic parameters of propofol are not affected by the administration of dexmedetomidine in healthy volunteers. Furthermore, dexmedetomidine and propofol show pharmacodynamic interaction for the sedation and suppression of the motor response.…”
Section: Discussionmentioning
confidence: 99%
“…The high volatility of isoflurane, coupled with low blood solubility, provided relatively rapid induction and recovery and easy control of the depth of anaesthesia. In another study, the recovery time has been reported to be significantly shorter after isoflurane anaesthesia, in comparison to propofol infusion in dexmedetomidine premedicated dogs (Kuusela et al 2003). The short recovery time observed in these groups might be caused by a lower blood gas partition coefficient of isoflurane and faster changes in the alveolar concentration that induced recovery from anaesthesia more rapidly than other inhalant anaesthetics.…”
Section: Time (Min)mentioning
confidence: 91%